2005
DOI: 10.1099/mic.0.27583-0
|View full text |Cite
|
Sign up to set email alerts
|

Two site-specific recombinases are implicated in phenotypic variation and competitive rhizosphere colonization in Pseudomonas fluorescens

Abstract: The biocontrol agent Pseudomonas fluorescens F113 undergoes phenotypic variation during rhizosphere colonization, and this variation has been related to the activity of a site-specific recombinase encoded by the sss gene. Here, it is shown that a second recombinase encoded by the xerD gene is also implicated in phenotypic variation. A putative xerD gene from this strain was cloned, and sequence analysis confirmed that it encoded a site-specific recombinase of the l integrase family. Mutants affected in the sss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 36 publications
(34 reference statements)
1
70
0
1
Order By: Relevance
“…The resulting mutants are impaired in cooperative group traits, such as extracellular enzymes and toxin production (Lapouge et al, 2008), but under laboratory conditions show an improved growth rate compared to their wild-type ancestors due to the cessation of secondary metabolism (Bull et al, 2001). Despite being weak competitors when inoculated alone (Natsch et al, 1994), gacS/gacA mutants multiply rapidly within soil pseudomonad populations (Chancey et al, 2002;Sanchez-Contreras et al, 2002;Martinez-Granero et al, 2005). Consequently, we hypothesized that these mutants gain advantage by exploiting the exoproducts of the wild-type population, with their competitiveness being the highest at low frequency in a dense wild-type population (Velicer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting mutants are impaired in cooperative group traits, such as extracellular enzymes and toxin production (Lapouge et al, 2008), but under laboratory conditions show an improved growth rate compared to their wild-type ancestors due to the cessation of secondary metabolism (Bull et al, 2001). Despite being weak competitors when inoculated alone (Natsch et al, 1994), gacS/gacA mutants multiply rapidly within soil pseudomonad populations (Chancey et al, 2002;Sanchez-Contreras et al, 2002;Martinez-Granero et al, 2005). Consequently, we hypothesized that these mutants gain advantage by exploiting the exoproducts of the wild-type population, with their competitiveness being the highest at low frequency in a dense wild-type population (Velicer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We use an isogenic signal-blind mutant of one of the used genotypes (Pseudomonas fluorescens CHA0DgacS 30 ) as model defector of defined genetic background. This mutant is typical for spontaneous mutations deactivating secondary metabolism in pseudomonads 28 and lacks extracellular proteases required for growing on albumin 3,30 . It grows better than the wild type when cooperation is not required 4 , but preliminary experiments showed that it is incapable of growing on QSM medium alone.…”
Section: Resultsmentioning
confidence: 99%
“…The phenotype of the isolated defectors is typical for mutations in the gacS/gacA QS cascade 27 , a rapidly mutating system whose deactivation results in signal blindness and accounts for virtually all protease-deficient mutants in Pseudomonas spp. 9,28 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations